Comparison of intravenous paracetamol vs. intramuscular diclofenac for postoperative pain control in abdominal hysterectomy - Bisht, Poonam; Jain, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Abdominal hysterectomy is one of the most common gynaecological surgery conducted worldwide. It is commonly associated with post operative pain. The aim of this study was Comparison of intravenous Paracetamol versus intramuscular Diclofenac for postoperative pain control in abdominal hysterectomy. Objectives of this study were to compare the effectiveness of intravenous Paracetamol and intramuscular Diclofenac when used for post-operative pain control in abdominal hysterectomy patients and to compare the need for rescue analgesia in both the groups. Methods: It’s a prospective observational and clinically randomized study conducted in Department of Obstetrics and Gynaecology, Government Medical College Haldwani and associated Dr. Shushila Tiwari Government Hospital, Haldwani consisting of 120 patients undergoing abdominal hysterectomy. 60 patients in group A received Paracetamol 1000 mg (100ml infusion) intravenous followed by subsequent doses of 1000 mg every 8 hourly for 48 hrs and another 60 patients in group B received injection Diclofenac 75 mg intramuscular every 8 hourly for 48hrs. Pain intensity of patients was noted 2 hourly for 6 hours after giving the first dose of the drug and then at every 8 hour for next 48 hours, using VAS scoring. Patient’s hemodynamics in form of respiratory rate, heart rate, mean arterial pressure (MAP), oxygen saturation (sPO2) were monitored as per pain monitoring protocol. Results: Post-op mean VAS score at different point of time among the two treatment groups was lower for Paracetamol group as compared to Diclofenac group. The difference was found to be statistically significant at all point of time post op. Adverse effect like nausea, vomiting and dizziness was seen more among Diclofenac group as compared to Paracetamol group. Conclusions: Intravenous Paracetamol use was found to be associated with better postoperative pain relief and reduced need for rescue analgesia consumption in the postoperative period.